The Modifiable Risk Factors of Uncontrolled Hypertension in Stroke: A Systematic Review and Meta-Analysis - Arif Setyo Upoyo; Ismail Setyopranoto; Heny Suseani Pangastuti (Stroke Research and Treatment)
Objective. This review aimed at figuring out the risk factors of uncontrolled hypertension in stroke. Method. This study systematically analyzed the hypertension risk factors available in the ProQuest, EBSCO, and PubMed databases published between 2010 and December 2019. The risk factors’ pooled odds ratio (POR) included in this research was calculated using both fixed and random-effect models. The meta-data analysis was processed using the Review Manager 5.3 (Rev Man 5.3). Result. Of 1868 articles, seven studies were included in this review searched using specific keywords. Based on the analysis results, there were 7 risk factors of uncontrolled hypertension in stroke: medication nonadherence (POR=2.23 [95% CI 1.71-2.89], p=0.342; I2=6.7%), use of antihypertensive drugs (POR=1.13 [95% CI 1.19-1.59, p=0.001; I2=90.9%), stage of hypertension (POR=1.14 [95% CI 1.02-1.27], p=<0.001; I2=97.1%), diabetes mellitus (POR=0.71 [95% CI 0.52-0.99], p=<0.001; I2=96.5%), atrial fibrillation (POR=1.74 [95% CI 1.48-2.04)], p=<0.001; I2=93.1%), triglycerides (POR=1.47 [95% CI 1.23-1.75], p=0.879; I2=0%), and age (POR=1.03 [95% CI 0.89-1.18], p=<0.001; I2=97.5%]. There were no bias publications among studies. Medication nonadherence and triglycerides had homogeneous variations, while the others had heterogeneous variations. Conclusion. Medication nonadherence, triglycerides, stage of hypertension, atrial fibrillation, and use of antihypertensive drugs significantly affect the uncontrolled hypertension in stroke.